Experimental investigation of dwell time characteristics in high-pressure double-solenoid-valve fuel injection system. (November 2019) - Xu, Dan; Yang, Qing; An, Xiaodong; Sun, Baigang; Wu, Dongwei; Zhang, Zhihao
The double-solenoid-valve fuel injection system consists of an electronic unit pump and an electronic injector. It can realize the separate control of fuel supply and injection and has the advantages of adjusting pressure by cycle and flexible controlling of the injection rate. The interval angle between the pilot and main injection directly affects the action degree and the characteristics of two adjacent injections, affecting engine performance. This work realizes multiple injection processes on the test platform of a high-pressure double-solenoid-valve fuel injection system, with maximum injection pressure reaching 200 MPa. In this study, the interval between driven current signal of pilot injection termination and that of main injection initiation is defined as the signal interval (DT1), whereas the interval between pilot injection termination and main injection initiation is defined as the injection interval (DT2). The differences between the signal and the injection intervals are calculated, and the variation rule of the difference with respect to the signal interval is analyzed. Results show that the variation rule of the difference with the signal interval first decreases, then increases, and finally decreases. The variation rule of the delay angle from the start of needle movement to the start of fuel injection is found to be the root cause of this rule. The influence of the injection pressure on needle deformation and fuel flow rate of the nozzle results in the variation rule. In addition, the influence of the cam speed, temperature, and pipe length on the difference between the signal and injection interval is determined. This research provides guidance for an optimal control strategy of the fuel injection process.